2013
DOI: 10.3892/ijmm.2013.1330
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of saponins derived from the roots of Platycodon grandiflorus in lipopolysaccharide-stimulated BV2 microglial cells

Abstract: Radix platycodi is the root of Platycodon grandiflorus A. DC, which has been widely used as a food material and for the treatment of a number of chronic inflammatory diseases in traditional oriental medicine. In this study, the anti‑inflammatory effects of the saponins isolated from radix platycodi (PGS) on the production of inflammatory mediators and cytokines in lipopolysaccharide (LPS)-stimulated BV2 murine microglial cells were examined. We also investigated the effects of PGS on LPS‑induced nuclear factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 55 publications
2
45
0
1
Order By: Relevance
“…Nevertheless, an additional possibility that non-neuronal cells, such as microglia, astrocytes, and endothelial cells, can also affect hippocampal synaptogenesis might be raised by previous studies reporting the protective effects of the root of PG against oxidative stress in the glioma cells [ 61 ] and inflammatory responses in microglial cells [ 34 ]. Furthermore, the present study is the first to examine the molecular signaling pathways underlying the PGE (root)-mediated enhancement of learning and memory, there might be a large number of signaling pathways involved in the effects of PGE (root) treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, an additional possibility that non-neuronal cells, such as microglia, astrocytes, and endothelial cells, can also affect hippocampal synaptogenesis might be raised by previous studies reporting the protective effects of the root of PG against oxidative stress in the glioma cells [ 61 ] and inflammatory responses in microglial cells [ 34 ]. Furthermore, the present study is the first to examine the molecular signaling pathways underlying the PGE (root)-mediated enhancement of learning and memory, there might be a large number of signaling pathways involved in the effects of PGE (root) treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In oriental traditional medicine, it is considered as a therapeutic constituent of medicines for amnesia and dementia, as well as inflammatory diseases [ 28 , 31 , 32 , 33 ]. Studies using the root of PG have demonstrated that PG attenuates lipopolysaccharide-induced inflammatory responses in microglial cells [ 34 ] and increases adult hippocampal neurogenesis by inducing neuronal cell proliferation in middle-aged mice [ 19 ]. Studies using specific components extracted from the root of PG have reported that triterpenes contained in the root of PG have protective effects against brain injury [ 28 , 35 , 36 ] and cognitive enhancing effects [ 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…16,17 NF-κB is able to bind to the specific promoter regions (that regulate the transcription of inflammatory genes) and for this reason it is a key regulator of inflammation. 18 The NF-κB transcription factor consists of p65 and p50 subunits, and is normally located (when in resting state) in the cytoplasm, bound to the inhibitory proteins IkBs (IkB-α, IkB-β, and IkB-ε). 19,20 The exposure of macrophages to pro-inflammatory stimuli causes a rapid phosphorylation of the IkB protein at two critical serine residues (Ser 32 and Ser 36) by IkB kinase (IKK).…”
Section: Introductionmentioning
confidence: 99%
“…A. DC., which is commonly known as bell flower or balloon flower, is an herbaceous perennial plant in the monotypic genus Platycodon in the Campanulaceae family (Jang et al, 2013). This species is native to China, Japan, Korea, and East Siberia (Wu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%